Evaluating Auditor Independence in Audit Engagements: A Case Study of Public Accounting Firm X - Nabila, Shafira Tasya; Martani, Dwi (E-Jurnal Akuntansi, 2026)
Auditor independence is the foundation of audit credibility, yet in practice it is often threatened by long-term relationships, fee dependency, and implicit client pressures particularly within medium-sized public accounting firms. This study aims to analyze the forms of independence threats that arise in audit practices at KAP X and evaluate the mitigation strategies implemented by auditors and the organization. Data were collected through in-depth interviews with partners, senior auditors, junior auditors, and regulators, as well as analysis of internal documents such as independence policies and independence declaration forms. The findings reveal four primary threats, self-interest, familiarity, intimidation, and self-review emerging through relational dynamics and economic pressures. Although mitigation strategies exist, they remain informal and rely heavily on partner leadership. The study concludes that auditor independence is more strongly shaped by ethical culture and daily practices than by structured quality control systems.